2007
DOI: 10.1210/jc.2006-1665
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profile in Omental Adipose Tissue in Women with Polycystic Ovary Syndrome

Abstract: The differences in the gene expression profiles in visceral adipose tissue of PCOS patients compared with nonhyperandrogenic women involve multiple genes related to several biological pathways, suggesting that the involvement of abdominal obesity in the pathogenesis of PCOS is more ample than previously thought and is not restricted to the induction of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
99
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 56 publications
20
99
1
3
Order By: Relevance
“…In contrast, a recent study found that adipose 11b-HSD1 was increased in women suffering from PCOS compared with healthy controls. 34 Two other studies have failed to show any polymorphisms in the HSD11B1 gene, and our results do not indicate reduced adipose cortisol production. 35,36 These results are not in line with our findings, possibly because of differences in study populations and methodology.…”
Section: Discussionsupporting
confidence: 46%
“…In contrast, a recent study found that adipose 11b-HSD1 was increased in women suffering from PCOS compared with healthy controls. 34 Two other studies have failed to show any polymorphisms in the HSD11B1 gene, and our results do not indicate reduced adipose cortisol production. 35,36 These results are not in line with our findings, possibly because of differences in study populations and methodology.…”
Section: Discussionsupporting
confidence: 46%
“…Another limitation is that only adipose tissue biopsies from one anatomical location were available for this study. Recently, genomic and proteomic profiling studies of morbidly obese PCOS omental adipose tissue have revealed changes in components of several biological pathways (34,35). Hence, there might be differences in the inflammatory status of visceral adipose tissue in women with PCOS (36).…”
Section: Discussionmentioning
confidence: 99%
“…Page 20 of 41 A c c e p t e d M a n u s c r i p t 20 As reported above, it is well known that ghrelin levels are negatively associated with obesity and positively with the insulin resistance state (Cortón et al, 2007;Shiiya et al, 2002).…”
Section: Ghrelin and The Polycystic Ovary Syndromementioning
confidence: 99%
“…Insulin resistance is very common in women with PCOS, particularly in the presence of obesity, and there is strong evidence this metabolic disorder, often associated with compensatory hyperinsulinemia, may play a triggering role in the pathophysiology of ovarian and adrenal hyperandrogenism, through different mechanisms described in detail elsewhere (Ehrmann 2005). Hyperandrogenism, in turn, may contribute to the generation of insulin resistance through the stimulation of lipolysis, and therefore the increased blood availability of FFA, and specific changes in muscle morphology, by increasing less insulin sensitive type 2 muscle fibers and decreasing the density of capillaries and glycogen content (Cortón et al, 2007). In addition, androgen excess may favor the enlargement of the visceral adipose tissue, which directly worsens insulin sensitivity.…”
Section: Ghrelin and The Polycystic Ovary Syndromementioning
confidence: 99%